Application of Organic Matter to Shallots Crop (Allium ascalonicum L.) - Arifah Sri Mursiani; Pangestika Padhina; Febriani Ade Ayu (BIO Web of Conferences)
The shallot crop (Allium ascalanicum L.) is one of the plants that has increased yearly, but as the community grows, consumption increases as well. This study aims to determine the effect of using different varieties and several types of animal manure compost. This study used a Randomized Block Design (RBD) arranged with two treatments and three replications. The first factor is the variety, which includes V1 (Thai), V2 (Bauji), and V3 (Bima), while the second factor is the type of compost, which includes J1 (goat manure compost), J2 (cow manure compost), and J3 (chicken manure compost). The research shows that there is an interaction between the fresh weight of bulbs per plant, the fresh weight of bulbs per plot, and the fresh weight of bulbs per hectare. The type of compost had no significant effect on the plant height, number of leaves, diameter of the bulb, dry weight of bulbs per plant, dry weight of bulbs per plot, and dry weight of bulbs per hectare. Treatment V1J1 (Thai varieties and goat manure compost) was the best treatment combination.